2014
DOI: 10.1007/s11010-014-2242-9
|View full text |Cite
|
Sign up to set email alerts
|

The novel role of TRPC6 in vitamin D ameliorating podocyte injury in STZ-induced diabetic rats

Abstract: Podocyte injury plays a critical role in the development and progression of diabetic nephropathy (DN). Over expression of TRPC6 on the podocytes has been revealed to cause podocyte injury in non-diabetic states. Besides, the emerging evidence from clinic revealed that vitamin D could reduce albuminuria and improve renal function, which was associated with podocyte protection. Our study aimed to investigate whether calcitriol ameliorating podocyte impairment is associated with regulation of the expression of TR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 48 publications
5
51
0
Order By: Relevance
“…The findings are principally in agreement with our data because retention of the NFκB subunits in the cytoplasma by prolonged binding to IκB-α subsequently destroys NFκB dimers [28]. Podocytes are apparently an important target of vitamin D3 and the hormone influences structure and function of podoyctes through various molecular mechanism [29,30,31,32]. In addition, activation of the NFκB-signaling pathway plays a major role in podocyte apoptosis [33,34,35], a pivotal feature of DN.…”
Section: Discussionsupporting
confidence: 90%
“…The findings are principally in agreement with our data because retention of the NFκB subunits in the cytoplasma by prolonged binding to IκB-α subsequently destroys NFκB dimers [28]. Podocytes are apparently an important target of vitamin D3 and the hormone influences structure and function of podoyctes through various molecular mechanism [29,30,31,32]. In addition, activation of the NFκB-signaling pathway plays a major role in podocyte apoptosis [33,34,35], a pivotal feature of DN.…”
Section: Discussionsupporting
confidence: 90%
“…61 This observation is consistent with many studies showing that VDR activators are renoprotective in models of proteinuric CKD. 123-125 In glomerular diseases, activation of VDR inhibits expression Wnt/β-catenin target genes such as Snail1 and TRPC6 , prevents podocyte injury and reduces proteinuria. 61,125 The VDR-mediated sequestration of β-catenin might therefore contribute to the renal protection of vitamin D analogues in proteinuric CKD.…”
Section: Strategies To Target Wnt/β-cateninmentioning
confidence: 99%
“…It has been widely reported that glomerular TRPC6 channels are substantially more abundant in type 1 and type 2 diabetes and in podocytes cultured in the presence of elevated external glucose . This is due at least in part to oxidative stress that can be driven by hyperglycemia, and by the surrounding pro‐inflammatory milieu .…”
Section: Introductionmentioning
confidence: 99%